2016
DOI: 10.1016/j.apergo.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Driving while using a smartphone-based mobility application: Evaluating the impact of three multi-choice user interfaces on visual-manual distraction

Abstract: a b s t r a c tInnovative in-car applications provided on smartphones can deliver real-time alternative mobility choices and subsequently generate visual-manual demand. Prior studies have found that multi-touch gestures such as kinetic scrolling are problematic in this respect. In this study we evaluate three prototype tasks which can be found in common mobile interaction use-cases. In a repeated-measures design, 29 participants interacted with the prototypes in a car-following task within a driving simulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Finally, completion time indicated that the two worst interfaces were the text-entry and slider widget which is congruent with earlier findings (Kujala, Silvennoinen, & Lasch, 2013;Louveton et al, 2016). Speed control and attention level were not sensitive to the different widgets.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, completion time indicated that the two worst interfaces were the text-entry and slider widget which is congruent with earlier findings (Kujala, Silvennoinen, & Lasch, 2013;Louveton et al, 2016). Speed control and attention level were not sensitive to the different widgets.…”
Section: Discussionsupporting
confidence: 89%
“…With a high penetration on mainstream market, touch-screen interactions such as those used on current smartphones are both familiar and easy-to-use due to the imprecise interactions required in finger pointing activity. However many studies showed that the type of widget used for a smartphone application impact differently driver's distraction (Kim & Song, 2014;Louveton et al, 2016). Additionally, it has been shown that text-entry and kinetic scrolling are the two major sources of visual-manual distraction in the car (Kujala, Silvennoinen, & Lasch, 2013).…”
Section: Mobile Devices and Visual-manual Distractionmentioning
confidence: 99%
“…This could turn input and selection into demanding tasks. While users needed to focus on mobile screen which required high visual attention, they also needed to pay attention to their environment at the same time [111]. Ng et al [112] found that input accuracy for tapping interaction dropped to 65% while users were walking and to 53% while they were carrying objects.…”
Section: Input Mode and Selectionmentioning
confidence: 99%
“…Louveton et al [111] assessed three different interface layouts and interaction: binary selection (e.g., yes/no), list selection, and slide bar. The results indicated that the binary selection was most efficient and demanded the lowest eye fixation, whereas the slide bar was least efficient and demanded the highest eye fixation [111]. However, more usability studies are needed to identify appropriate layouts and interaction for in-car interactive systems.…”
Section: Input Mode and Selectionmentioning
confidence: 99%
“…Moreover, an effective scrolling technique in the mobile device is an interesting topic for many specialized environments. For example, in the automotive industry, interacting with the large amounts of data on a mobile device while driving is an important challenge, wherein scrolling is considered as one of the typical interactions [13,14]. In this study, we present adaptive kinetic scrolling (AKS), a scrolling technique that permits rapid access to target information in an ordered large dataset based on the user's scrolling actions and the amount of data to be scrolled.…”
Section: Introductionmentioning
confidence: 99%